2011
DOI: 10.1098/rspb.2011.1424
|View full text |Cite
|
Sign up to set email alerts
|

Grandparental investment and reproductive decisions in the longitudinal 1970 British cohort study

Abstract: There has been a recent increase in interest among evolutionary researchers in the hypothesis that humans evolved as cooperative breeders, using extended family support to help decrease offspring mortality and increase the number of children that can be successfully reared. In this study, data drawn from the 1970 longitudinal British cohort study were analysed to determine whether extended family support encourages fertility in contemporary Britain. The results showed that at age 30, reported frequency that pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 28 publications
1
55
2
2
Order By: Relevance
“…Waynforth [117] found that, among a British cohort born in 1970, financial dependency on parents delayed and limited reproduction, but being close to parents and seeing parents frequently increased reproduction between ages 30 and 34 years. Time-based kin support may be more important than resource-based kin support in encouraging fertility.…”
Section: (K) Cooperative Breeding and Kin Supportmentioning
confidence: 99%
“…Waynforth [117] found that, among a British cohort born in 1970, financial dependency on parents delayed and limited reproduction, but being close to parents and seeing parents frequently increased reproduction between ages 30 and 34 years. Time-based kin support may be more important than resource-based kin support in encouraging fertility.…”
Section: (K) Cooperative Breeding and Kin Supportmentioning
confidence: 99%
“…This support may signal to a woman that it is both feasible and desirable to have an additional family member (Sear and Dickins 2010). In modern, resource-rich countries, emotional support received from grandparents could have a greater influence on fertility decisions than practical assistance with child care (Waynforth 2011).…”
Section: Grandparental Child Care Help and Emotional Supportmentioning
confidence: 99%
“…Grandparental child care help has been found to be correlated with an increased probability that parents will have another child in the Netherlands (Kaptijn et al 2010;Thomese and Liefbroer 2013), and one study has detected a positive association between grandparental child care help and childbearing in several European countries if the grandchildren were not very young (Aassve, Meroni, and Pronzato 2012). By contrast, Waynforth (2011) found no association between grandparental child care and parents' fertility in the UK, although the closeness of the parents to their own parents was shown to be associated with an increased likelihood of having another child. The possible positive effect of grandparental help is thus relatively weak, and can be expected to vary by country and parity, as well as by the type and the availability of grandparental investment.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship is found only among employed women. Several European studies have also shown a positive association between parental help and the likelihood of childbearing (for example, Kaptijin et al 2010;Waynforth 2012). One shortcoming of these studies is their failure to control for the provision of alternative formal childcare, which may substitute for parental help.…”
Section: Help From Parents and Parents-in-lawmentioning
confidence: 99%
“…Evidence has been found for links between higher fertility rates and 1) the husband's contributions to domestic work (Cooke 2004(Cooke , 2009De Laat and SevillaSanz 2011;Feyrer, Sacerdote, and Stern 2008;Nagase and Brinton 2017;Park, Cho, and Choi 2010;Park 2012), 2) help with childcare from parents or parents-in-law (Morgan and Hirosima 1983;Kaptijin et al 2010; Thomese and Liefbroer 2013;Waynforth 2012;Zhang 1990), and 3) the availability and affordability of formal childcare services (Gauthier 2007;Rindfuss et al 2007). …”
Section: Introductionmentioning
confidence: 99%